Fingalian Topographies: Ossian and the Highland Tour, 1760‐1805. (June 2016) - Leask, Nigel
Abstract: If Ossian validated the Highland landscape for eighteenth‐century tourists, the landscape, in turn, seemed to authenticate poems whose authenticity never ceased to be doubted; but text and topography alike ran the risk of dissolving into insubstantiality. Many tourists cited 'local tradition' in order to embroider existing (or to invent new) Fingalian place‐names. Ranging over a wide variety of eighteenth‐century travel‐writers, this article casts new light on the relations between Ossian, travel‐writing and Highland topography. It concludes by discussing the 'fieldwork' tradition of Ossianic tourism after 1800, which sought out local tradition bearers, rather than attempting to authenticate Macpherson's 'translations'.